Un discurso clave no proceso de canonización da obra de Rosalía de Castro: La poesía regional gallega (1885) de Emilia Pardo Bazán - Pardo Amado, Diego (Madrygal. Revista de Estudios Gallegos, 2010)
The course of critical reception of Rosalía of Castro´s work was influenced by Emilia Pardo Bazan, whose writing consolidates a process of canonization that, in spite of Murguía and Rosalia desires, perpetrates a harmful and pernicious interpretation of the Galician poet. In this article, we analyze an important text for Galician literature, considering different elements that determined the possition of the Countess, the reasons of her polemic with Murguia and the subsequent situation.
Keywords: Emilia Pardo Bazan; Rosalia´s critique; Canonization; Literary Galician system; Regionalism